Rapid and reliable diagnosis of Moraxella catarrhalis infection using loop-mediated isothermal amplification-based testing - Xiao, Fei; Zhou, Juan; Huang, Xiaolan; Fu, Jin; Jia, Nan; Sun, Chunrong; Xu, Zheng; Wang, Yi; Yu, Lei; Meng, Lihui (Frontiers in Bioengineering and Biotechnology, 2024)
Moraxella catarrhalis (M. catarrhalis) was an important pathogen closely associated with respiratory tract infections. We employed the loop-mediated isothermal amplification (LAMP) coupled with nanoparticle-based lateral flow biosensor (LFB) and fluorescence testing technique for formulating two diagnostic methods for M. catarrhalis detection, termed M. catarrhalis-LAMP-LFB assay and M. catarrhalis-LAMP-FRT, respectively. The M. catarrhalis-LAMP-LFB system incorporated the use of biotin-14-dCTP and a forward loop primer (LF) with a hapten at the 5' end.This design in LAMP reaction enabled the production of double-labeled products that could be effectively analyzed using the lateral flow biosensor (LFB). For the M. catarrhalis-LAMP-FRT assay, the LF was modified with a sequence at 5' end, and a fluorophore, as well as a black hole quencher, were strategically labeled at the 5' end and within the middle of the new LF. The restriction endonuclease Nb.BsrDI could accurately recognize and cleave the newly synthesized double-strand terminal sequences, resulting in the separation of the fluorophore from the black hole quencher and releasing fluorescence signals. Both assays have been proven to be highly sensitive and specific, capable of detecting genomic DNA of M. catarrhalis at concentrations as low as 70 fg, with no cross-reactivity observed with non-M. catarrhalis pathogens. Furthermore, both methods successfully identified M. catarrhalis in all clinical samples within 1 h that were confirmed positive by real-time PCR, exhibiting superior sensitivity than conventional culture methods. Herein, the newly developed two LAMP-based assays were rapid and reliable for M. catarrhalis detection and hold significant promise for deployment in point-of-care (POC) settings.